Human Rights in Cuba, El Salvador, and Nicaragua : a Sociological Perspective on Human Rights Abuse. - Gómez, Mayra (Studies in international relations (Routledge (Firm)), 2003)
Illuminates the inter-play between national and international levels of analysis, by addressing long-term patterns of human rights abuse in Cuba, El Salvador and Nicaragua, from the late 1960s and 70s to the present day.